DEVELOPING A NATURAL SCIENCE LEARNING VIDEO OF HUMAN RESPIRATORY SYSTEM FOR THE FIFTH GRADERS AT SDN 1 TELAGA USING SIMPLE MATERIALS - Gamar Abdullah; Rustam I Husain (FIP Unimed, 2022)
This research aims to develop a natural science learning video of the human respiratory system using simple materials. We used Borg and Gall’s model yet in a limited manner as we only used the five initial stages the model required, i.e., (1) finding the potentials and problems, (2) collecting information and literature studies, (3) designing the product, (4) validating the design, and (5) revising the design. Research data were collected using observation and interview methods. Findings indicate that the mean of the validity score of visual media and materials included in learning media was 93.33% and 94.54%, respectively.